Perancangan Aplikasi Media Pembelajaran Pengenalan Hewan Berbasis Virtual Reality Menggunakan Platform Android - I Made Artawan; Made Sudarma; I Made Arsa Suyadnya (Program Studi Teknik Elektro UNUD, 2017)
Natural science (IPA) is a subject that is intended to allow students to have an organized concept of the natural surroundings. Learn science as a way of helping students to understand more deeply the natural surroundings. One material science lessons given in fourth grade elementary school to discuss the grouping animals based on the type of food. On the subject matter students are expected to be able to tell the difference between herbivores, carnivores and omnivores. Currently the teachers at the school only uses conventional teaching methods with the book medium for conveying the material. Media books or conventional learning media can not provide a real visualization of the shape of animals. Animal grouping based learning problems in elementary school, learning media applications based animal recognition virtual reality created to help elementary school students in recognizing the object animal. Application development starts from the concept stage, design, collection of materials, assembly, testing, until the distribution phase. This application is built using the programming language C #, google cardboard SDK, software blender and unity. The result obtained is an application that can be used as a learning medium introduction of animals. In the introduction of animal learning media applications users can run, can see the types of herbivores, carnivores and omnivores are already equipped with information, sound and animation. Based on the test results with the Black-Box, functional applications have been able to run well and based ontest the System Usability Scale result average value of 20 respondents was 80.25 with Scale Grade B.